Evaluating the Effect of Repetitive Transcranial Magnetic Stimulation on Disorders of Consciousness by Using TMS-EEG - Bai, Yang; Xia, Xiaoyu; Kang, Jiannan; Yin, Xiaoxiao; Yang, Yi; He, Jianghong; Li, Xiaoli (Frontiers in Neuroscience, 2016)
Background: The modulation efficacy of Transcranial magnetic stimulation (TMS) on consciousness improvement of patient with disorder of consciousness (DOC) has not been definitely confirmed. Objective: This study proposes TMS-EEG to assess effects of repetitive TMS (rTMS) on brain modulation of DOC. Methods: Twenty sessions of 10Hz rTMS were applied over the dorsolateral prefrontal cortex for a patient with DOC. Measures of Coma Recovery Scale-Revised (CRS-R) score, TMS-evoked potential (TEP), perturbation complexity index (PCI) and global mean field power (GMFP) were used to evaluate the consciousness level of the patient at three intervals: before the rTMS protocol (T0), immediately after one session rTMS (T1) and immediately after twenty sessions (T2). Results: It was found that the patient was diagnosed of a minimally conscious state minus (MCS-) by means of CRS-R at the interval of T0, however the TEP and PCI indicated the patient was vegetative state (VS). At the interval of T1, there was not any clinical behavioral improvement in CRS-R, but we could find significant changes in TEP, PCI and GMFP. At the interval of T2 there was a significant increase of consciousness level according by CRS-R score, PCI value, TEP and GMFP after twenty sessions of 10Hz rTMS on the patient with DOC. Conclusions: We demonstrated that TMS-EEG might be an efficient assessment tool for evaluating rTMS protocol therapeutic efficiency in DOC.